Contralateral acupuncture for migraine without aura: a randomized trial protocol with multimodal MRI - Chen, Ziwen; Li, Qifu; Lu, Yi; Huang, Gaoyangzi; Huang, Ya; Pei, Xianmei; Gong, Yi; Zhang, Bingkui; Tang, Xin; Liu, Zili; Guo, Taipin; Liang, Fanrong (Frontiers in Neuroscience, 2024)
Introduction Migraine is a common clinical disorder, ranks as the second most disabling disease worldwide, and often manifests with unilateral onset. Contralateral acupuncture (CAT), as a classical acupuncture method, has been proven to be effective in the treatment of migraine without aura (MWoA). However, its neural mechanisms have not been investigated using multimodal magnetic resonance imaging (MRI). Methods and analysis In this multimodal neuroimaging randomized trial, a total of 96 female MWoA participants and 30 female healthy controls (HCs) will be recruited. The 96 female MWoA participants will be randomized into three groups: Group A (CAT group), Group B [ipsilateral acupuncture (IAT) group], and Group C (sham CAT group) in a 1:1:1 allocation ratio. Each group will receive 30 min of treatment every other day, three times a week, for 8 weeks, followed by an 8-week follow-up period. The primary outcome is the intensity of the migraine attack. Data will be collected at baseline (week 0), at the end of the 8-week treatment period (weeks 1–8), and during the 8-week follow-up (weeks 9–16). Adverse events will be recorded. Multimodal MRI scans will be conducted at baseline and after 8-week treatment. Discussion This study hypothesized that CAT may treat MWoA by restoring pathological alterations in brain neural activity, particularly by restoring cross-integrated functional connectivity with periaqueductal gray (PAG) as the core pathological brain region. The findings will provide scientific evidence for CAT in the treatment of MWoA. Ethics and dissemination The Medical Ethics Committee of the Second Affiliated Hospital of Yunnan University of Chinese Medicine has given study approval (approval no. 2022-006). This trial has been registered with the Chinese Clinical Trials Registry (registration no. ChiCTR2300069456). Peer-reviewed papers will be used to publicize the trial’s findings. Clinical trial registration https://clinicaltrials.gov/, identifier ChiCTR2300069456.